The Role of Subsequent Conduct in Border Disputes - أحمد, بسام (Latakia University Journal - Economic and Legal Sciences Series, 2020)
The subsequent conduct of the parties of border treaties or arbitral decisions has a crucial role in judgments rendered by international courts, and occupies a large part of the proceedings of the parties before the courts. The subsequent conduct is all statements, maps and correspondence issued by the parties of the dispute. Furthermore, sovereign acts in the conflict zone operated by states parties is considered as a subsequent conduct. States probably do this subsequent conduct either with the knowledge of its effects which are wanted to be arranged or with ignorance of these effects. Therefore, this conduct might be evidence used by other States before international justice and arbitration. Due to the importance of the evidence of the subsequent conduct in resolving the dispute before the jurisdiction and arbitration, we will highlight its meaning, conditions, effects "in accordance with the Vienna Convention on the Law of Treaties", international relation and jurisprudence. in order to guide the official authorities in exercising their (Legislative, executive and judicial) functions and to realize its effect at the international level.